Application of charging effects in evaluating storage space of tight reservoirs: A case study from Permian Lucaogou Formation in Jimusar sag, Junggar Basin, NW China - Xiaoqi WANG; Liang SUN; Rukai ZHU; Xu JIN; Jianming LI; Songtao WU; Lina BI; Xiaodan LIU (Petroleum Exploration and Development, 2015)
According to the study of the electron beam charging effects of oil-bearing samples from tight reservoirs, a “Two-step Cross-section Back Scattered Electron (BSE) Imaging Method” is put forward, revealing the distribution of residual oil (the oil without loss in the vacuum conditions) in the tight reservoir. With the injection of charging agent, the connectivity of the pore system can also be characterized by this method, and a novel quantitative method of evaluating the effectiveness of reservoir space is established. For the tight reservoir samples from the Permian Lucaogou Formation in the Jimusar sag in the Junggar Basin, which was taken as an example, the strong charging effects mainly result from the residual oil in pores. The oil from pyrolysis of organic matter was widely stored in the pores both inside and nearby organic matter, or existing in poor organic matter area. Due to the super-large analyzing area, the Two-step Cross-section BSE Imaging Method can solve the weak representation of analysis area caused by the heterogeneity. The method of injection of charging agent works well in revealing the connectivity of the pore system. The total plane porosity of oil-bearing samples from the tight reservoir of the Lucaogou Formation is 12.56%, and the connectivity of the whole pore system in the sample reaches as high as 90%. The effectiveness of the reservoir space is very high. Key words: electron beam charging effect, Two-step Cross-section BSE Imaging, effective reservoir space, pore connectivity, tight oil, Junggar Basin, Jimusar sag, Lucaogou Formation